2019
DOI: 10.3390/pharmacy7040148
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise Pharmacist-Led Medication Review Service in Interdisciplinary Teams in Rural Nursing Homes

Abstract: Background: The provision of responsible medication therapy to old nursing home residents with comorbidities is a difficult task and requires extensive knowledge about optimal pharmacotherapy for different conditions. We describe a stepwise pharmacist-led medication review service in combination with an interdisciplinary team collaboration in order to identify, resolve, and prevent medication related problems (MRPs). Methods: The service included residents from four rural Norwegian nursing homes during August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For this reason, the Spanish Society of Primary Care Pharmacists (SEFAP), based on Milton et al [ 65 ], recommends reviewing medication every 6 months for NH residents with polypharmacy, and at least once a year for the rest of institutionalised people. Furthermore, other authors concluded that it is necessary to integrate the pharmacist into NH in interdisciplinary collaboration with doctors and nurses to identify, solve and prevent DRP [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Spanish Society of Primary Care Pharmacists (SEFAP), based on Milton et al [ 65 ], recommends reviewing medication every 6 months for NH residents with polypharmacy, and at least once a year for the rest of institutionalised people. Furthermore, other authors concluded that it is necessary to integrate the pharmacist into NH in interdisciplinary collaboration with doctors and nurses to identify, solve and prevent DRP [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the study documented that the rates of DRPs varied up to seven-fold (from 0.5 to 3.4) between the NHs. To the best of our knowledge, only two medication review studies have previously reported variation in DPRs between NHs: one in two urban NHs, from 3.0 to 5.5 mean DRPs per patient [ 20 ] and another study in four rural NHs, from 2.7 to 5.6 mean DRPs per patient [ 30 ]. The mean of 2.0 DRPs per patient found in the total cohort is below those previously reported in Norway [ 2 , 3 , 13 ], probably because we reported DRPs agreed upon by the team, not all DRPs suggested by the pharmacist.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important limitation that we have only recorded the DRPs that were accepted by the physicians, without recording all the DRPs that were initially suggested by the pharmacists. Hence, we do not know how the physicians' acceptance rates varied between the different NHs and how appropriate their rejections were [30]. Some doctors may have experienced suggestions to change their treatment as a threat and criticism towards their own prescribing practice.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…nervous system ADRs in drugs affecting the cardiovascular system). This underlines the complexity of geriatric patient treatment and the need for interdisciplinary medication reviews that include an assessment of drug-related problems, such as drug-drug interactions, potentially inappropriate medication, as well as ADRs [ 25 , 26 ]. In routine care, however, potential additive effects are often not taken into account.…”
Section: Discussionmentioning
confidence: 99%